1970
DOI: 10.1128/aem.19.4.557-564.1970
|View full text |Cite
|
Sign up to set email alerts
|

Arbovirus Identification by an Agar-Gel Diffusion Technique

Abstract: A double diffusion-in-agar test was used to investigate precipitation reactions of 75 arboviruses. Specific reactions were regularly observed with members of arbovirus groups B, California, Simbu, Turlock, Hart Park, vesicular stomatitis, and several other arboviruses as well as with a member of the Tacaribe group and a herpesvirus. The results demonstrated the feasibility of applying this technique to the identification of arboviruses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

1971
1971
2004
2004

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 7 publications
1
8
0
Order By: Relevance
“…The Bunyaviridae are a newly defined family of lipid-enveloped RNA viruses that appear to possess segmented RNA genomes (17). By serological analyses, about 90 bunyaviruses have been divided into 11 groups with some, but not all, members of each group being serologically related to one or more members of another group (1,4,8,9,17,26,27). These 11 groups constitute the Bunyamwera supergroup of viruses of different groups are not known.…”
mentioning
confidence: 99%
“…The Bunyaviridae are a newly defined family of lipid-enveloped RNA viruses that appear to possess segmented RNA genomes (17). By serological analyses, about 90 bunyaviruses have been divided into 11 groups with some, but not all, members of each group being serologically related to one or more members of another group (1,4,8,9,17,26,27). These 11 groups constitute the Bunyamwera supergroup of viruses of different groups are not known.…”
mentioning
confidence: 99%
“…Of 92 cases diagnosed as California (LAC) virus infections and for which all three test results were available, we diagnosed 4 (4.3%) by HI alone, 8 (8.7%) by CF alone, 8 (8.7%) by N alone, 2 (2.2%) by HI and CF, 34 (37.0%) by HI and N, 3 (3.3%) by CF and N, and 33 (35.9%) by all three techniques. Figure 1 shows the geometric mean titers, by time after reported disease onset, for 284 sera collected from the 128 individuals.…”
Section: Resultsmentioning
confidence: 99%
“…Infections with LAC subtype may be diagnosed serologically by hemagglutination inhibition (HI) (6), complement fixation (CF) (4), neutralization (N) (12), agar gel precipitation (3), fluorescent antibody (C. L. Frazier, personal communication), enzyme-linked immunosorbent assay (B. Beaty, personal communication), or electrophoresis (15). The first three techniques, however, represent the primary methods by which nearly all infections caused by LAC and other California serogroup viruses are diagnosed.…”
mentioning
confidence: 99%
“…Double agar gel ID studies of the CAL group arboviruses first were reported by Murphy and Coleman in 1967 (11). ID techniques have been employed by several investigators to type CAL virus isolates and to detect precipitin antibodies in woodland animals (3,13,14). However, the ID system has not been used extensively for the identification of human CAL infections (3,10,11).…”
Section: Discussionmentioning
confidence: 99%
“…ID techniques have been employed by several investigators to type CAL virus isolates and to detect precipitin antibodies in woodland animals (3,13,14). However, the ID system has not been used extensively for the identification of human CAL infections (3,10,11). The CEP system, which recently has been utilized in the diagnosis of hepatitis B (12), influenza (2), and certain bacterial (4) and fungal (5) infections, has not been applied to arboviruses to our knowledge.…”
Section: Discussionmentioning
confidence: 99%